Tryptophan degradation enzymes expression in the placenta and the Kynurenine/Tryptophan ratio in maternal plasma after elective cesarean section. (March 2023) - Silvano, Angela; Seravalli, Viola; Strambi, Noemi; Vallario, Arianna; Tofani, Lorenzo; Parenti, Astrid; Di Tommaso, Mariarosaria
Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1) and tryptophan 2, 3-dioxygenase (TDO) metabolize tryptophan in the kynurenine pathway. We evaluated these enzymes' mRNA expression in maternal and fetal sides of the placenta of uncomplicated, unlabored full-term pregnancies after elective cesarean section and compared it with that of placentas obtained from vaginal delivery. Tryptophan and kynurenine plasmatic levels after cesarean section were measured, to investigate their possible correlation with IDO1 and TDO mRNA (TDO2) expression. The results suggested that IDO1 and TDO2 expression was higher in the maternal side of the placenta and that labor significantly affects TDO2 expression and the plasma Kynurenine/Tryptophan ratio.